Pandaragupan redeveloping the Riverfront Market Complex as a catalyst for urban sustainability and resilience in downtown Dagupan - Ngilay, Helena M.
Downtowns as the main street of development often act as the core of a city's economic, political, cultural, and religious life. However, many downtown areas in the Philippines are suffering the negative effects of rapid urbanization. Being the core of the city, downtowns are most commonly where public markets are located, vital to the city functions as a source of basic commodities and livelihood. Unfortunately, along with the declining state of downtown areas are the run-down conditions of public markets as well. This study uses public market redevelopments as a catalyst for urban sustainability and resilience in Philippine downtowns, as in the case of Dagupan City. With Downtown Dagupan's location along one of the city's major river subsidiaries, the public market site offers great potential but is faced with the challenge of being in a hazard prone area. Redeveloping the public markets of Dagupan addresses concerns on commerce, local industry, tourism, and transport by providing a design centered on the human dimension that is equipped with new construction technologies and flood mitigation strategies.